2009
DOI: 10.1245/s10434-009-0551-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CXCR4 in Primary Tumor of Patients with HER-2 Negative Breast Cancer was Predictive of a Poor Disease-Free Survival: A Validation Study

Abstract: We validated that high CXCR4 overexpression in primary tumors of patients with HER-2 negative tumors portend a poor outcome. These findings should be confirmed with either a prospective clinical trial and/or an external validation study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…While the possibility of “overfitting” our data certainly exists, we believe that there may be some biologic basis to this cut‐off point. Our group has demonstrated CXCR4's prognostic significance when the cut‐off points were chosen within this range 23, 24. However, an internal validation study using another group of patients or an external validation study using either another data set and/or multi‐institutional trials will be required to validate these findings.…”
Section: Discussionmentioning
confidence: 89%
“…While the possibility of “overfitting” our data certainly exists, we believe that there may be some biologic basis to this cut‐off point. Our group has demonstrated CXCR4's prognostic significance when the cut‐off points were chosen within this range 23, 24. However, an internal validation study using another group of patients or an external validation study using either another data set and/or multi‐institutional trials will be required to validate these findings.…”
Section: Discussionmentioning
confidence: 89%
“…Forty-seven studies, with a total of 5,592 patients, included data on progress free survival in 12 types of cancer 8, 10, 12, 14-27, 31-33, 35, 38-40, 43, 45-48, 53, 56, 63-66, 70, 73, 75, 77-80, 82, 83, 85, 88, 89]. Of all the participants, 2583 (46%) were CXCR4 over-expression.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled model showed a significantly shorter PFS with CXCR4 over-expression patients in hematological malignancy (6 studies, 537 patients, HR=2.31, 95% CI, 1.33-4.02, Figure 3) [12, 14-18], breast cancer (13 studies, 2318 patients, HR=1.80, 95% CI, 1.31-2.45, Figure 4) [10, 19-27, 30, 32, 33], colorectal cancer (4 studies, 263 patients, HR=2.69, 95% CI, 1.70-4.26, Figure 5) [35, 38-40], esophageal cancer (5 studies, 760 patients, HR=1.59, 95% CI, 1.24-2.05, Figure 6) [43, 45-48], renal cancer (4 studies, 488 patients, HR=3.98, 95% CI, 2.26-7.01, Figure 7) [63-66], gynecologic cancer (6 studies, 466 patients, HR=3.03, 95% CI, 1.89-4.88, Figure 8) [77-80, 82, 83] and liver cancer (2 studies, 256 patients, HR=2.32, 95% CI, 1.73-3.10) [88, 89]. Based on the available data, the associations between CXCR4 over-expression and PFS were inconclusive in gastric cancer (1 studies, 26 patients, HR=3.42, 95% CI, 0.71-16.36) [53], head and neck cancer (1 studies, 71 patients, HR=1.19, 95% CI, 0.56-2.54) [56], lung cancer (2 studies, 233 patients, HR=1.05, 95% CI, 0.12-8.96) [8, 70], melanoma (2 studies, 103 patients, HR=1.42, 95% CI, 0.64-3.19) [73, 75], pancreatic cancer (1 studies, 71 patients, HR=1.28, 95% CI, 0.90-1.83) [85].…”
Section: Resultsmentioning
confidence: 99%
“…18,19,[27][28][29] The use of tumor CXCR4 expression as a prognostic tool to predict outcome after partial hepatectomy for metastatic colorectal cancer has only been analyzed in one previous study. 25 Kim et al 25 demonstrated in a retrospective analysis of 29 patients that CXCR4 tumor expression was associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%